The Role of Artificial Intelligence as a Transformation of Learning in the Modern Era - Muhammad Gafarurrozi; Moh. Fatkur Rohman; Rizal Fathurrohman (International Journal of Science and Applied Science: Conference Series, 2024)
Abstract: In today's modern era, the world of education has experienced changes in the learning system. In recent years, artificial intelligence has emerged as a transformative force in the education system in the modern era. This research aims to analyze the role of artificial intelligence in transforming learning in the modern era. The method used in this research is library research. The data collected is in the form of journal articles, research reports, and documents related to the topic discussed in this research. The analysis in this research uses content analysis. The research results show that the role of artificial intelligence in the learning process has a significant role. The use of artificial intelligence technology can provide an independent learning experience. Students can search for material according to their needs, and learning methods using artificial intelligence technology can increase student involvement, thereby creating high motivation in students. Therefore, artificial intelligence has great potential in transforming learning systems in the modern era. On the one hand, artificial intelligence can be a solution in the learning process in the modern era. And on the other hand, artificial intelligence can be a challenge in the world of education. Thus, to make maximum use of artificial intelligence requires caution regarding academic ethical issues.